POLITICAL POSTS NUANCES IN THE PUBLIC SERVICE SYSTEM IN THE TRANSPORT SECTOR - Armash, Nadiia O.; Kozyreva, Valentyna P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Aim: to study the peculiarities of the legal status of state political figures in the transport sphere. Submit the views of scientists to the problem of duality of these categories of employees. Methods of research: while writing the article, methods of analysis and synthesis were used. Widely used comparative method of research. Results: The authors offer their views on the normative base of this category of civil servants. Opinions about the nature of discretionary powers as features of political positions in the transport sector are also outlined. Discussion: peculiarities of the national legislation and the prospect of implementation of the provisions of foreign legislation to the domestic legislation in the transport sphere.